Roles, processes, and outcomes of interprofessional shared decision-making in a neonatal intensive care unit: A qualitative study. Issue 3 (4th May 2018) - Dunn, Sandra I.; Cragg, Betty; Graham, Ian D.; Medves, Jennifer; Gaboury, Isabelle
ABSTRACT: Shared decision-making provides an opportunity for the knowledge and skills of care providers to synergistically influence patient care. Little is known about interprofessional shared decision-making processes in critical care settings. The aim of this study was to explore interprofessional team members' perspectives about the nature of interprofessional shared decision-making in a neonatal intensive care unit (NICU) and to determine if there are any differences in perspectives across professional groups. An exploratory qualitative approach was used consisting of semi-structured interviews with 22 members of an interprofessional team working in a tertiary care NICU in Canada. Participants identified four key roles involved in interprofessional shared decision-making: leader, clinical experts, parents, and synthesizer. Participants perceived that interprofessional shared decision-making happens through collaboration, sharing, and weighing the options, the evidence and the credibility of opinions put forward. The process of interprofessional shared decision-making leads to a well-informed decision and participants feeling valued. Findings from this study identified key concepts of interprofessional shared decision-making, increased awareness of differing professional perspectives about this process of shared decision-making, and clarified understanding of the different roles involved in the decision-making process in an NICU.